Recht und Realität: Festschrift für Christoph Vedder - Lorenzmeier, Stefan; Folz, Hans-Peter (Nomos, 2017)
The festschrift for Christoph Vedder contains 42 contributions of reknown scholars in the areas of European law, European External Relations law, Public International Law , German public law and sports law. They are analysing recent issues like the brexit, data protection, the EEA and arbitration in sports law.With contributions byFinn Arnesen, Christoph Becker, Roland Bieber, Astrid Epiney, Ulrich Fastenrath, Hans-Peter Folz, Ulrich Gassner, Rudolf Geiger, Thomas Giegerich, Volkmar Götz, Hans Petter Graver, Christoph Gusy, Ulrich Haas, Wolff Heintschel von Heinegg, Waldemar Hummer, Hubert Isak, Daniel-Erasmus Khan, Gregor Kirchhof, Martin Kment, Andreas Kumin, Josef Franz Lindner, Ola Mestad, Thomas M.J. Möllers, Peter-Christian Müller-Graff, Ingo von Münch, Roman Petrov, Thilo Rensmann, Michael Rodi, Marcus Schladebach, Rudolf Streinz, Christa Tobler, Joachim Wieland, Ferdinand Wollenschläger
Gesehen am 03.08.2017
Keywords: Aufsatzsammlung; Festschrift; Bibliografie; Sportrecht; Recht; Deutschland; Völkerrecht; Europäische Union; Vedder, Christoph; Staatsrecht; Europarecht